Medea by Euripides: Triadic and Symmetrical Composition According to the Content (Minerva, 2017)
Euripides’ tragedy Medea shows a strong tendency to structure the whole work and the individual parts in triads as well as in axial symmetry. The whole play can be divided into three parts, each one also tripartite, whose distribution is closely related to the content: Part I (prologue + parodos + episode 1) presents the preliminaries or causes; Part II (episode 2 + episode 3 ―centre― + episode 4, flanked by the correspondent stasima 1, 2, 3 and 4) is developing the plot towards the conclusion; Part III (episode 5 + last stasimon + exodos) already presents the consequences, the conclusion. The central element (episode 3) of part II is not only the compositional but also the thematic core, since the μεταβολὴ τῆς τύχης is located there. Besides, it is the numerical epicentre of the play. The parallelism between the two elements (episodes 2 and 4) that frame the central part is evident, and thereby the central part shows axial symmetry. There is also axial symmetry and correspondence between the extreme parts (I and III).
Keywords: tragedy; Medea; Euripides; symmetry; triadic composition; composition; content